Halal Food Industries and Learning Organization - Aini, Ahmad; Nordin, Norhaslinda (2015)
Learning organization is one of a famous management term and has been widely discussed. However, the applicability of this concept with halal industries has yet to be explored. The purpose of this paper are: (a) to share the concept of halal industries, little known in the west, which may stimulate further discussion and debate on its relationship with management practices i.e the learning organization, and (b), to provide some knowledge of Islamic view on learning organization in order to help managers do business in Muslim culture in general and in growing halal industries in particular. The paper concludes with business implications and suggestion for further research